Temporal Release of Fatty Acids and Sugars in the Spermosphere: Impacts on Enterobacter cloacae-Induced Biological Control - Windstam, Sofia; Nelson, Eric B (Applied and Environmental Microbiology, 2008)
The aim of this study was to determine the temporal release of fatty acids and sugars from corn and cucumber seeds during the early stages of seed germination in order to establish whether sugars found in exudate can prevent exudate fatty acid degradation by Enterobacter cloacae. Both saturated (long-chain saturated fatty acids [LCSFA]) and unsaturated (long-chain unsaturated fatty acids [LCUFA]) fatty acids were detected in corn and cucumber seed exudates within 15 min after seed sowing. LCSFA and LCUFA were released at a rate of 26.1 and 6.44 ng/min/seed by corn and cucumber seeds, respectively. The unsaturated portion of the total fatty acid pool from both plant species contained primarily oleic and linoleic acids, and these fatty acids were released at a combined rate of 6.6 and 0.67 ng/min/seed from corn and cucumber, respectively. In the absence of seed exudate sugars, E. cloacae degraded linoleic acid at rates of 29 to 39 ng/min, exceeding the rate of total fatty acid release from seeds. Sugars constituted a significant percentage of corn seed exudate, accounting for 41% of the total dry seed weight. Only 5% of cucumber seed exudate was comprised of sugars. Glucose, fructose, and sucrose were the most abundant sugars present in seed exudate from both plant species. Corn seeds released a total of 137 μg/seed of these three sugars within 30 min of sowing, whereas cucumber seeds released 0.83 μg/seed within the same time frame. Levels of glucose, fructose, and sucrose found in corn seed exudate (90 to 342 μg) reduced the rate of linoleic acid degradation by E. cloacae to 7.5 to 8.8 ng/min in the presence of either sugar, leaving sufficient concentrations of linoleic acid to activate Pythium ultimum sporangia Our results demonstrate that elevated levels of sugars in the corn spermosphere can prevent the degradation of LCUFA by E. cloacae, leading to its failure to suppress P. ultimum sporangial activation, germination, and subsequent disease development.